2004
DOI: 10.1074/jbc.m403607200
|View full text |Cite
|
Sign up to set email alerts
|

The LETM1/YOL027 Gene Family Encodes a Factor of the Mitochondrial K+ Homeostasis with a Potential Role in the Wolf-Hirschhorn Syndrome

Abstract: Respiring mitochondria maintain a membrane potential (⌬⌿) 1 of Ϫ150 to Ϫ180 mV (⌬⌿, inside negative). This high ⌬⌿ constitutes a large driving force for the electrophoretic influx of cations, either through specific channels or by diffusion through the membrane. Several cation channels have been characterized physiologically (reviewed in Refs. 1 and 2), and recently, a single one has been identified molecularly (3). These transport systems seem to have intrinsic control mechanisms which ensure that the matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
247
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(268 citation statements)
references
References 32 publications
17
247
1
Order By: Relevance
“…LETM1 encodes a ubiquitously expressed leucine zipper-EF-handcontaining transmembrane 1 protein 18 with intracellular localization to mitochondria 36,37 and the ER. 38 Its cellular function as an ion exchanger [37][38][39][40][41] suggests potential roles in cell signaling and energy production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LETM1 encodes a ubiquitously expressed leucine zipper-EF-handcontaining transmembrane 1 protein 18 with intracellular localization to mitochondria 36,37 and the ER. 38 Its cellular function as an ion exchanger [37][38][39][40][41] suggests potential roles in cell signaling and energy production.…”
Section: Discussionmentioning
confidence: 99%
“…38 Its cellular function as an ion exchanger [37][38][39][40][41] suggests potential roles in cell signaling and energy production. In flies and worms, LETM1 loss-of-function causes severe growth restriction and decreased viability.…”
Section: Discussionmentioning
confidence: 99%
“…Its product is an integral protein of the inner mitochondrial membrane, and is well conserved among all eukaryotes. 6 Hemizygous deletion in humans has been invoked as causing a major part of the Wolf-Hirschhorn disease phenotype. 7 The presence of a putative EF Ca 2 þ binding hand domain within almost all Mdm38p homologues suggested a role for Mdm38p in mitochondrial Ca 2 þ homeostasis and morphology.…”
mentioning
confidence: 99%
“…Mutants deleted for this gene have functional defects of mitochondria, reduced growth of cells on non-fermentable substrate (petite phenotype), a nearly complete loss of mitochondrial K þ (Na þ )/H þ exchange activity, high K þ matrix content, low membrane potential (Dc), and dramatically increased volume. 6,9 Recently, Frazier et al (2006) noted reduced amounts of certain mitochondrially encoded proteins in the inner membrane despite their translation efficiency being unchanged. They found that protein A-tagged Mdm38p formed complexes with mitochondrial ribosomes, and suggested that the reduced amount of some of the mitochondrially encoded proteins of complexes III, IV, and V resulted from the lack of Mdm38p interacting with mitochondrial ribosomes to mediate membrane insertion of several proteins of nuclear and mitochondrial origin.…”
mentioning
confidence: 99%
See 1 more Smart Citation